2015
DOI: 10.1371/journal.pone.0135267
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Quality of Life with Service Satisfaction in Psychotic Patients: A Meta-Analysis

Abstract: BackgroundQuality of life (QoL) has gained increasing attention as a desired outcome of psychosocial treatments targeting psychotic patients. Yet, the relationship between the patients’ satisfaction with services and QoL has not been clearly established, perhaps due to the multidimensionality of the QoL concept and the variability in its assessment.AimThis is the first systematic meta-analysis of all available evidence assessing the relationship between QoL and service satisfaction. Methods: In all, 19 studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 76 publications
1
17
0
5
Order By: Relevance
“…Elevated levels of user satisfaction with services were also associated with better quality of life in previous studies of individuals with serious MHD (Furrer et al, ; Nasrallah, Targum, Tandon, McCombs, & Ross, ; Petkari & Pietschnig, ), which seems reasonable. Perceptions of being appropriately treated may also have positive effects for quality of life (Nasrallah et al, ; Petkari & Pietschnig, ), as may positive user assessments of service quality (e.g. adequacy of staff, and quality of information received; Petkari & Pietschnig, ).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Elevated levels of user satisfaction with services were also associated with better quality of life in previous studies of individuals with serious MHD (Furrer et al, ; Nasrallah, Targum, Tandon, McCombs, & Ross, ; Petkari & Pietschnig, ), which seems reasonable. Perceptions of being appropriately treated may also have positive effects for quality of life (Nasrallah et al, ; Petkari & Pietschnig, ), as may positive user assessments of service quality (e.g. adequacy of staff, and quality of information received; Petkari & Pietschnig, ).…”
Section: Discussionmentioning
confidence: 57%
“…According to the literature, frequent health services users are also those who receive inadequate treatment or insufficient continuity of care; they are often high users of emergency departments in particular (Richard-Lepouriel et al, 2015). Elevated levels of user satisfaction with services were also associated with better quality of life in previous studies of individuals with serious MHD (Furrer et al, 2018;Nasrallah, Targum, Tandon, McCombs, & Ross, 2005;Petkari & Pietschnig, 2015), which seems reasonable. Perceptions of being appropriately treated may also have positive effects for quality of life (Nasrallah et al, 2005;Petkari & Pietschnig, 2015), as may positive user assessments of service quality (e.g.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Researchers exploring the relationship between satisfaction with care and QoL among patients with serious mental illness have largely reported a positive relationship between the two [52,53]. Nevertheless, studies investigating the causal nature of this relationship have remained sparse, and thus far, only a few have found a positive association between satisfaction with care and QoL among those patients [28,54]. Thus, our results might be even more useful for interventions among clinicians to make them more aware of patients who are unsatisfied early in their care.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a published study found that sociodemographic and clinical factors, such as marital status, income and somatic or psychological comorbidities, explained differences in QoL changes between alcohol-dependent twins and their abstinent cotwins [27]. Similarly, the relationship between patients' satisfaction with care and QoL changes has not been clearly established among populations with psychiatric disorders [28]. Patient satisfaction can be defined as an individual's cognitive evaluation of and emotional reaction to his or her health care experience [29,30].…”
Section: Introductionmentioning
confidence: 99%